2020
DOI: 10.1017/s1352465820000156
|View full text |Cite
|
Sign up to set email alerts
|

Self-concept, post-traumatic self-appraisals and post-traumatic psychological adjustment: what are the relationships?

Abstract: Background:Cognitive models of post-traumatic psychological adjustment have implicated both self-concept and self-appraisals in post-traumatic stress disorder (PTSD). Two studies investigated the relationship between self-concept and trauma-related self-appraisals, and whether culture influenced this relationship.Method:In Study 1, a student sample (Asian n = 41, British n = 34) who self-identified as having been through a trauma or extremely stressful event completed measures of self-concept, trauma-related s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…At the cognitive level, the negative perception of self, feeling of bitterness, feeling of helplessness, and revengeful thoughts were among the cultural script elements identified. The literature has indicated that all of these script elements are mental representations and practices that are still comprehensible but understood as abnormal and undesirable (Chentsova-Dutton et al, 2014) and that they are influenced by culture (Engelbrecht and Jobson, 2020). Nevertheless, this study shed light on survivors' perception of why these script elements occur in the studied population.…”
Section: Discussionmentioning
confidence: 75%
“…At the cognitive level, the negative perception of self, feeling of bitterness, feeling of helplessness, and revengeful thoughts were among the cultural script elements identified. The literature has indicated that all of these script elements are mental representations and practices that are still comprehensible but understood as abnormal and undesirable (Chentsova-Dutton et al, 2014) and that they are influenced by culture (Engelbrecht and Jobson, 2020). Nevertheless, this study shed light on survivors' perception of why these script elements occur in the studied population.…”
Section: Discussionmentioning
confidence: 75%
“…Psychological research indicates that one of the many consequences of trauma is that it negatively impacts an individual's self-concept (e.g. self-esteem and confidence; Engelbrecht and Jobson, 2020). In the context of police–community engagement initiatives, African Australians who are navigating trauma may lack the self-confidence to engage in certain activities and may be fearful or weary of police presence during engagement initiatives.…”
Section: Section IImentioning
confidence: 99%
“…For example, we tend to evaluate ourselves in the present by comparing ourselves to the future self we hope to achieve (Bak, 2015). Related to this, neurocognitive findings have consistently linked PTSD to negative self-evaluations (Engelbrecht & Jobson, 2020).…”
Section: Mental Time Travelmentioning
confidence: 99%